Letters to my Palestinian neighbor - Klein Halevi, Yossi, 1953- (Harper, an imprint of HarperCollinsPublishers, 2018)
"Letters to My Palestinian Neighbor is one Israeli's powerful attempt to reach beyond the wall that separates Israelis and Palestinians and into the hearts of "the enemy." In a series of letters, Yossi Klein Halevi explains what motivated him to leave his native New York in his twenties and move to Israel to participate in the drama of the renewal of a Jewish homeland, which he is committed to see succeed as a morally responsible, democratic state in the Middle East." -- Amazon.com.